Mutation and Phylogenetic Analysis of Spike Glycoprotein of Indonesian Isolates of Severe-Acute-Respiratory-Syndrome-Coronavirus-2 (SARS-CoV-2) - Shabarni Gaffar; Syifa Al Fauziah Rahmani; Ari Hardianto (Faculty of Medicine, Universitas Padjadjaran, 2021)
Coronavirus disease-2019 (COVID-19) is an infectious acute respiratory disease caused by SARS-CoV-2. The protein that plays a role in the entry of SARS-CoV-2 into human cells is the surface protein, or the Spike, which is thought to be the effective vaccine target to prevent SARS-CoV-2 infection. Until December 2020, Indonesia has reported 106 SARS-CoV-2 genome sequences identified from COVID-19 positive patients. The purpose of this study was to analyze the phylogenetic relationship of the Spike protein of the Indonesian isolates of SARS-CoV-2 Indonesian, as well as the virus mutations and their effects on changes in the amino acid. The 106 Indonesian SARS-CoV-2 genomes were downloaded from GISAID and the Spike nucleotide and amino acid sequences were analyzed by multiple sequence alignment (MSA) and mutation analysis using the ClustalW method. Phylogenetic trees were created using the Neighbor-Joining method in MEGA-X software. The results showed that 30 of the 106 Indonesian isolate SARS-CoV-2 Spike were 100% identical to the Wuhan-Hu-1, while the remaining 76 had experienced mutations at 1-4 sites. There were 43-point mutations in the Spike gene, 27 of which led to amino acid changes and four had not been reported in other countries. The global mutation D614G was found in 60 Indonesian isolates , of which West Java was the province with the most reports. The phylogenetic of Spike showed that the Indonesian samples have been divided into several branches that are far from Wuhan-Hu-1. This study indicates the possibility of differences in the protein structure of Indonesian isolate SARS-CoV-2 Spike that need to be further studied to manufacture a vaccine against the Indonesian strain of SARS-CoV-2.